THE ANALYSIS OF FINANCIAL STATEMENTS OF COOPERATIVE EMPLOYEES BIMA KARYA PU BENGKULU SELATAN - Mega Leby Sartiana; Neri Susanti; Novman Ahmad Ali (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
The purpose of this research is to find out the financial performance in “Koperasi Bima Karya” South of Bengkulu from 2014 to 2016 which can be seen from financial report. Data analysis technique which is used in this research are Time Series and Cross section analysis. Time series is a measurement method of financial report by comparing financial report and observe the koperasi financial ration from certain period. Cross Section method is a benchmark method which is used to decided if the koperasi financial is good or not by comparing the financial ratio on certain period. According to result and analysis, it can be concluded that fund ratio from 2014 to 2016 generally is 12,88% means in 3 years, Koperasi Bima Karya, south of Bengkulu is in good condition because it can pay short term debt from smooth assets. In quality ratio of production active is generally in 2014 to 2016 is in 8,33% means the Koperasi runs well because it can pay short- and long-term debt. For Efficiency ratio, Koperasi Bima Karya south of Bengkulu from 2014 to 2016 can be concluded is in 50,02% means the Koperasi is efficient because in last 3 years, the Koperasi Bima Karya, south of Bengkulu can obtain profit.